Submarine platform development by erosion of a Surtseyan cone at Capelinhos, Faial Island, Azores. Issue 15 (9th September 2019) - Zhao, Zhongwei; Mitchell, Neil C.; Quartau, Rui; Tempera, Fernando; Bricheno, Lucy
Abstract: Erosion of volcanic islands ultimately creates shallow banks and guyots, but the ways in which erosion proceeds to create them over time and how the coastline retreat rate relates to wave conditions, rock mass strength and other factors are unclear. The Capelinhos volcano was formed in 1957/58 during a Surtseyan and partly effusive eruption that added an ~2.5 km 2 tephra and lava promontory to the western end of Faial Island (Azores, central North Atlantic). Subsequent coastal and submarine erosion has reduced the subaerial area of the promontory and created a submarine platform. This study uses historical information, photos and marine geophysical data collected around the promontory to characterize how the submarine platform developed following the eruption. Historical coastline positions are supplemented with coastlines interpreted from 2004 and 2014 Google Earth images in order to work out the progression of coastline retreat rate and retreat distance for lava‐ and tephra‐dominated cliffs. Data from swath mapping sonars are used to characterize the submarine geometry of the resulting platform (position of the platform edge, gradient and morphology of the platform surface). Photographs collected during SCUBA and ROV dives on the submarine platform reveal a rugged surface now covered with boulders. The results show that coastal retreat rates decreased rapidly with time after the eruption and approximately follow an inverse power‐law relationship with coastal retreat distance. We develop a finite‐difference model for wave attenuation over dipping surfaces to predict how increasing wave attenuation contributed to this trend. The model is verified by reproducing the wave height variation over dipping rock platforms in the UK (platform gradient 1.2° to 1.8°) and Ireland (1.8°). Applying the model to the dipping platform around Capelinhos, using a diversity of cliff resistance predicted from known lithologies, we are able to predict erosion rate trends for some sectors of the edifice. We also explore wider implications of these results, such as how erosion creates shallow banks and guyots in reef‐less mid‐oceanic archipelagos like the Azores. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : Post‐eruptive coastline retreat of the Capelinhos promontory was rapid at first but has since slowed dramatically, leaving behind a submarine dipping platform. The results reveal that coastal retreat rates decreased rapidly with time after eruption and approximately follow an inverse power‐law relationship with retreat distance. We develop a finite‐difference model for attenuation over dipping surfaces to predict how increasing wave attenuation contributed to this trend.